Injuries in Youth and National Combined Events Championships - Edouard, P.; Samozino, P.; Escudier, G.; Baldini, A.; Morin, J.-B. (International Journal of Sports Medicine, 2012)
In major track and field competitions, the most risky discipline is the combined event. Therefore, we aimed to record and analyze the incidence and characteristics of sports injuries incurred during the Youth and National Combined Events Championships. During the French Athletics Combined Events Championships in 2010, all newly occurred injuries were prospectively recorded by the local organising committee of physicians and physiotherapists working in the medical centres at the stadium, in order to determine incidence and characteristics of newly occurred injuries. In total, 51 injuries and 9 time-loss injuries were reported among 107 registered athletes, resulting in an incidence of 477 injuries and 84 time-loss injuries per 1 000 registered athletes. Approximately 72% of injuries affected lower limbs and 60% were caused by overuse. Thigh strain (17.6%) was the most common diagnosis. 14 dropouts were recorded, 8 were caused by an injury (57.1%). During the National and Youth Combined Events Championships, over one third of the registered athletes incurred an injury, with an injury incidence higher than in international elite track and field competitions. Interestingly, this higher injury risk concerned the younger population affecting immature musculoskeletal structures. In combined events, preventive interventions should mainly focus on overuse and thigh injuries.
Keywords: sports injury prevention; athletics; epidemiology; adolescents; championships; track and field